Mitochondrial DNA Polymorphism of the European Roe Deer, Capreolus capreolus (Artiodactyla, Cervidae), from the South-West of Ukraine - Zvychaynaya, E. Yu.; Звычайная, Е. Ю.; Volokh, Anatolii; Волох, Анатолий Михайлович; Волох, Анатолій Михайлович; Kholodova, M. V.; Холодова М. В.; Danilkin, A. A.; Данилкин, А. А. (My University, 2013)
EN: Analysis of mtDNA control region (934 b. p.) and cytochrome b gene (1140 b. p.) polymorphism of the 33 roe deer samples from the south-west of Ukraine was carried out. 30 different haplotypes of mtDNA have been described and all of them are related to Capreolus capreolus Linnaeus, 1758. Two well differentiated haplogroups were discovered on the examined territory. The isolated subgroup of related haplotypes was revealed in the Crimea that is likely a result of the long-term geographical isolation of the Crimean roe deer populations. RU: Проведен анализ полиморфизма контрольного региона (934 н. п.) и гена цитохрома b мтДНК (1140 н. п.) 33 образцов косули юго-западной Украины. Описано 30 разных гаплотипов мт ДНК, все они принадлежатCapreolus capreolus Linnaeus, 1758. На исследованной территории обнаружены две хорошо дифференцированные гаплогруппы с обособленной подгруппой близких гаплотипов в Крыму, что скорее всего, является следствием длительной географической изоляции популяции косули Крымского полуострова.
Полиморфизм митохондриальной ДНК европейской косулиCapreolus capreolus (Artiodactyla, Cervidae), юго-западной Украины
Keywords: European roe deer; Siberian roe deer; Capreolus; range; population; haplogroups; gene; control region; cytochrome b gene; mtDNA; европейская косуля; сибирская косуля; ареал; популяция; гаплогруппы; ген цитохрома b; мтДНК